EFEKTIVITAS EDUKASI KESEHATAN “AYO BERSIH AYO SEHAT” MENGENAI CUCI TANGAN PAKAI SABUN DAN PEMILIHAN JENIS SAMPAH PADA SISWA DI SDN 13 RAMBANG - Najma Hoirunnisa; Adelina Irmayani Lubis; Dinda Putri Maharani; Zurriyati Azka Ramadhani; Nazila Safitri; Popi Anjani; Siti Mahaida; Mukaddimah Najwa Al Yusna; Arista Miranda Putri; Sarila Diva Dea Ariesty; Fatimah Nur Mutmainah; Naura Rizky Deprianty; Ari Tri Gusti (PARIPALAKA SRIWIJAYA, 2025)
Health education activities are one of the promotive and preventive efforts in instilling the values ​​of clean and healthy living behavior (PHBS) from an early age. In the context of implementing the community service program, an educational activity with the theme "Ayo Bersih, Ayo Sehat" was carried out at SDN 13 Rambang on May 26, 2025. The target of the activity was 44 students in grades 4 to 6 who were given learning through Participatory Learning and Action approach. The main focus of this activity is the introduction and direct practice of Washing Hands with Soap (CTPS) and sorting types of waste as part of healthy and environmentally friendly behavior. Students are given an explanation of the material using leaflets and demonstrations then invited to practice the six steps of CTPS using a decorative bucket facility specially designed for this activity. The CTPS song is also used to help students remember the stages of washing their hands more easily. In addition, an understanding of the types of waste is conveyed through interactive sticker map media, which makes it easier for students to classify organic, inorganic, and B3 waste. The results of the activity show that creative and interactive educational methods can improve students' knowledge and skills in maintaining personal and environmental hygiene. The high enthusiasm of students and the accuracy in practice indicate that learning involving visual media and direct activities is more effective in forming healthy behavior. Therefore, similar activities can be an applicable health education model in other elementary school environments